2019
DOI: 10.3310/hsdr07370
|View full text |Cite
|
Sign up to set email alerts
|

Alternative community-based models of care for young people with anorexia nervosa: the CostED national surveillance study

Abstract: Background Evidence suggests that investing in specialist eating disorders services for young people with anorexia nervosa could have important implications for the NHS, with the potential to improve health outcomes and reduce costs through reductions in the number and length of hospital admissions. Objectives The primary objectives were to evaluate the costs and cost-effectiveness of alternative community-based models of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Inpatient hospital activity for children with eating disorders showed particularly steep increases [ 31 ], despite evidence showing that hospital care is not the best first line option [ 47 ]. Specifically, research indicates that family treatment outside of the hospital setting and specialist community services may be more effective than general child and adolescent mental health services (CAMHS) for treating young people with eating disorders [ 48 ]. Admissions for depression and schizophrenia were also rising faster among children than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient hospital activity for children with eating disorders showed particularly steep increases [ 31 ], despite evidence showing that hospital care is not the best first line option [ 47 ]. Specifically, research indicates that family treatment outside of the hospital setting and specialist community services may be more effective than general child and adolescent mental health services (CAMHS) for treating young people with eating disorders [ 48 ]. Admissions for depression and schizophrenia were also rising faster among children than adults.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases managed was also considered important but consensus was not achieved on how many were required to signify specialist expertise. An economic evaluation of specialist v. generic eating disorder services for young people suggested that specialist services did not produce better outcomes but as they worked with young people who had more severe difficulties, they were costeffective depending on willingness to pay (Byford et al, 2019). It is intuitively plausible that a combination of regional highly specialist services to provide training, consultation and direct work with those with complex difficulties could compliment more widespread support in generic adult mental health teams, but proper evaluation is as desperately needed.…”
Section: Service Organisation and Transitional Care Modelsmentioning
confidence: 99%
“…It is harder than might first be imagined to define what constitutes a specialist service. A Delphi study 94 conducted about this issue in relation to eating disorders concluded that specialist services providing evidence-based interventions must be multi disciplinary, and staff working within the service must have a clear focus on, and expertise in, the focus condition. The number of cases managed was also considered important, but consensus was not achieved on how many were required to signify specialist expertise.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Correction for unreturned BPSU/CAPSS notification cards. To account for incidence among unreturned cards, a correction to the observed incidence rate was applied, using two assumptions as suggested by Petkova et al 94 in a previous study:…”
Section: Analysis Of Surveillance Datamentioning
confidence: 99%